The role of credit on the evolution of wealth inequality in the USA - Rodolfo Oviedo Moguel (Banco de México, 2020)
In the USA, the share of household wealth held by the richest 1% increased from 23.5% in 1980 to 41.8% in 2012. This paper contributes to understanding the causes behind this increase. First, using an accounting decomposition, I show that more than half of the increase in the share of the top 1% can be attributed to a decrease in the saving rate of the bottom 99%. Second, using a heterogeneous agent model, I show that the decrease in the saving rate of the bottom groups cannot be rationalized by the reduction in the progressively of taxation or changes in the volatility and concentration of labor earnings. Lastly, I introduce a shock to the credit market into the model in the form of loosening the borrowing constraints of the economy. This shock can simultaneously match the increase in wealth concentration and the decrease of the saving rate of the economy.
Keywords: D14; D31; D33; E21; E62; G51; 330; Credit; Debt; Saving Rate; Wealth Distribution